Computerized videodefecography versus defecography: do we need radiographs? - Sobrado, Carlos Walter; Pires, Carlos Eduardo Fonseca; Araújo, Sergio Eduardo Alonso; Amaro, Edson; Habr-Gama, Angelita; Kiss, Desidério Roberto (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Defecography has been recognized as a valuable method for evaluating patients with evacuation disorders. It consists of the use of static radiography and ﬂuoroscopy to record different situations within anorectal dynamics. Conventionally, rectal pa- rameters are measured using radiograms. It is rare for ﬂuoroscopy alone to be used. Computer software has been developed with the speciﬁc aim of calculating these measurements from digitized videotaped images obtained during ﬂuoroscopy, without the need for radiographic ﬁlm, thereby developing a computerized videodefecography method. The objective was thus to compare measurements obtained via computerized videodefecography with conventional measurements and to discuss the advantages of the new method. DESIGN AND SETTING: Prospective study at the radiology service of Hospital das Clínicas, Universidade de São Paulo. METHOD: Ten consecutive normal subjects underwent videodefecography. The anorectal angle, anorectal junction, puborectalis muscle length, anal canal length and degree of anal relaxation were obtained via the conventional method (using radiography ﬁlm) and via computerized videodefecography using the ANGDIST software. Measurement and analysis of these parameters was performed by two independent physicians. RESULTS: Statistical analysis conﬁrmed that the measurements obtained through direct radiog- raphy ﬁlm assessment and using digital image analysis (computerized videodefecography) were equivalent. CONCLUSIONS: Computerized videodefecography is equivalent to the traditional defecography examination. It has the advantage of offering reduced radiation exposure through saving on the use of radiography.